Selective endodontic retreatment of mandibular molar with apical periodontitis - case report (Research, Society and Development, 2022)
Objective: This paper aims to report a clinical case diagnosed with asymptomatic apical periodontitis at the clinic of the Specialization Course in Endodontics at Universidade São Paulo, addressing the indications and techniques performed, as well as clinical and radiographic aspects. Indications for selective retreatment include cases in which the treatment was carried out for more than 1 year, teeth with satisfactory coronal restorations and no direct exposure of the root canal filling to the oral cavity, absence of periodontal disease, multirooted teeth with bone rarefactions periapical lesions in only one root, being confirmed by Cone Beam Computed Tomography (CBCT) analysis. Case Report: The patient in question sought the Fundecto-USP (FFO) specialization clinic for endodontic retreatment of tooth 36. In the tomographic evaluation, the location of the DL canal was not located and not previously treated. Retreatment was performed only on the root whose canal had not been located, and which had periapical bone rarefaction. Final considerations: The selective retreatment of roots with apical periodontitis can be another viable form of conservative treatment in endodontics when well indicated in cases where there is no exposure of the filling material and the retreatment of all roots can cause the risk of weakening the tooth structure and tooth loss.